2008
DOI: 10.1073/pnas.0711159105
|View full text |Cite|
|
Sign up to set email alerts
|

Mycobacterial persistence requires the utilization of host cholesterol

Abstract: A hallmark of tuberculosis is the ability of the causative agent, Mycobacterium tuberculosis , to persist for decades despite a vigorous host immune response. Previously, we identified a mycobacterial gene cluster, mce4 , that was specifically required for bacterial survival during this prolonged infection. We now show that mce4 encodes a cholesterol import system that enables M. tuberculosis to derive both carbon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
1,039
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 939 publications
(1,103 citation statements)
references
References 45 publications
36
1,039
3
2
Order By: Relevance
“…In Mycobacterium tuberculosis, this property is manifested as an ability to attract cholesterol into the lipid-free zone that surrounds the cell wall mycolic acid layer [146] and is at the basis of the requirement for host cell membrane cholesterol to enable entry of the bacillus into its host macrophage [139,147]. Besides being essential for the phagocytosis of the bacterium by the macrophage, cholesterol is also used by the bacilli as an energy and carbon source that is critically linked with mycobacterial persistence [148,149] and depends on a sufficient availability of the sterol within the host cell. Mycolic acids may in fact constitute a direct means by which intracellular M.…”
Section: Cholesteroid Nature Of Mycolic Acidsmentioning
confidence: 99%
“…In Mycobacterium tuberculosis, this property is manifested as an ability to attract cholesterol into the lipid-free zone that surrounds the cell wall mycolic acid layer [146] and is at the basis of the requirement for host cell membrane cholesterol to enable entry of the bacillus into its host macrophage [139,147]. Besides being essential for the phagocytosis of the bacterium by the macrophage, cholesterol is also used by the bacilli as an energy and carbon source that is critically linked with mycobacterial persistence [148,149] and depends on a sufficient availability of the sterol within the host cell. Mycolic acids may in fact constitute a direct means by which intracellular M.…”
Section: Cholesteroid Nature Of Mycolic Acidsmentioning
confidence: 99%
“…Interestingly, it has been described that only fast-growing non-pathogenic mycobacteria were able to grow on cholesterol as a sole carbon source (Av-Gay & Sobouti, 2000); however, more recent results have demonstrated that cholesterol is also used as a carbon source during infection of M. tuberculosis (Pandey & Sassetti, 2008). Although recent biochemical and structural studies have assigned a role for some of the mycobacterial genes in cholesterol catabolism, the complete degradative pathway and its specific regulation remain to be fully established (Capyk et al, 2009;Knol et al, 2008;Lack et al, 2010;Yam et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the identification of conserved domains in many Mce proteins, previous studies strongly suggest that the mce and yrbE genes encode components of ABC transport systems (Kumar et al, 2005;Casali & Riley, 2007). Moreover, it has recently been demonstrated that mce4 encodes a cholesterol import system that enables M. tuberculosis to derive both carbon and energy from host cholesterol (Pandey & Sassetti, 2008). Interestingly, Kendall et al (2007) have shown that the mce4 operon is regulated by KstR, a TetR-type regulator, and co-regulated with other genes involved in fatty acid metabolism.…”
Section: Introductionmentioning
confidence: 99%